Penguatan Keputusan Pembelian Konsumen Produk Motor Berbasis Kualitas Produk, Promosi Penjualan Dan Persepsi Harga: Studi Kasus Pada Konsumen Motor Satria F150 Suzuki Di Wilayah Kota Bogor - Gendalasari, Gen Gen; Hawari, Muhammad Diwas; Zuhdi, Saefudin (Program Vokasi dan LPPM IBI Kesatuan, 2024)
In the modern era like now, transportation is a means that is really needed by society. This is due to the progress of the times and the increasing standard of living of people's needs. Various transportation is available, one of which is motorbikes. The decision to purchase a product is currently greatly influenced by various other factors such as product quality, and the usefulness of a product as well as external factors such as: Sales Promotion and Price Perception. Therefore, it is important to conduct research to find out how product quality, sales promotion and price perception influence motorbike product purchasing decisions. The purpose of this research is to determine the influence of each dimension of Product Quality, Sales Promotion and Price Perception. This research used quantitative methods, and data collection was carried out by distributing online questionnaires to the people of Bogor City, with a sample size of 200 people. Research data was processed using SPSS 25. The analysis method used is multiple regression analysis. The results of this research are as follows: (1) Product quality has a positive and significant effect on product purchasing decisions with a regression coefficient value of 0.126 and a significant value of 0.000. (2) Sales promotions have a positive and significant effect on purchasing decisions with a regression coefficient value of 0.222 and a significant value of 0.000. (3) Price perception has a positive and significant effect on purchasing decisions with a regression coefficient value of 0.322 and a significant value of 0.000. (4) Product Quality, Price Perception and Promotion have a positive and significant effect on purchasing decisions for the Satria F150 Suzuki motorbike product with a calculated F value of 20.658 and greater than the F table of 2.65 and has a significance value of 0.000. Keywords: Product Quality, Sales Promotion, Price Perception and Purchasing Decisions